The reactive–proactive aggression questionnaire: validation among a Portuguese sample of incarcerated juvenile delinquents - Pechorro, Pedro Fernandes dos Santos (2018)
The aim of the present study was to examine the psychometric properties of the Reactive–Proactive Aggression Questionnaire (RPQ) among a forensic sample of incarcerated male juvenile offenders (N = 221). The Portuguese version of the RPQ demonstrated promising psychometric properties, namely, in terms of factor structure, internal consistency, convergent validity, discriminant validity, and concurrent validity that generally justifies its use among this population. Statistically significant associations were found with conduct disorder, age of criminal onset, age of first problem with the law, crime seriousness, physical violence use in committing crimes, alcohol use, cannabis use, cocaine/heroin use, and having unprotected sex. The findings provide additional support for the extension of the RPQ across different cultures, ethnic groups, and samples.